2016
DOI: 10.3233/ais-160396
|View full text |Cite
|
Sign up to set email alerts
|

From interactive surfaces to interactive game pieces in hybrid board games

Abstract: Recent advances in interactive surfaces and Tangible User Interfaces (TUIs) have created new opportunities for hybrid board games that aim at mixing the social affordances of traditional board games with the interactivity of video games. Within this area of research, we propose an approach centered on the concepts of tokens, constraints, spatial expressions, and interaction events. Rather than using interactive surfaces as the primary interaction medium, our approach relies on physical manipulation of interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
1
8
0
2
Order By: Relevance
“…Mora et al [23] reported on a thorough investigation on the benefits and general design space of interactive game pieces in the direction of hybrid games. They argued to focus on physical manipulation of interactive, computer-augmented physical artifacts on conventional surfaces rather than creating interactive surfaces for hybrid games.…”
Section: Hybrid Perspectives On Digital-physical Playmentioning
confidence: 99%
See 1 more Smart Citation
“…Mora et al [23] reported on a thorough investigation on the benefits and general design space of interactive game pieces in the direction of hybrid games. They argued to focus on physical manipulation of interactive, computer-augmented physical artifacts on conventional surfaces rather than creating interactive surfaces for hybrid games.…”
Section: Hybrid Perspectives On Digital-physical Playmentioning
confidence: 99%
“…For the design of hybrid remote interactions, we argue to go a step further and try to integrate the "computation" into the physical materials themselves (e.g., in the direction of computational meta-materials that integrate computational functionality embedded in the very physical material itself, beyond embedded electronics [76,77]). In that regard, Mora et al [23] provided a thorough argument to go beyond the design of interactive surfaces but focus on the design of interactive game pieces in hybrid boardgames. In this direction of integrating computation into the physical material (e.g., for the implementation of reactive boardgame pieces), a new category of seemingly smart materials would be added to the palette of (remote) boardgame design that are inherently hybrid.…”
Section: Tracking Technology To Enable Bodily Signals-designing For Nmentioning
confidence: 99%
“…Mora, Loreto e Divitini [10] discorrem que jogos analógicos proporcionam experiências sociais engajadoras, compostas por dois níveis de interação: entre os próprios jogadores, presencialmente, e também entre os jogadores e os elementos físicos do jogo. Segundo elas, essa experiência é facilitada por interações tangíveis, físicas e sociais, que envolvem elementos comuns presentes em vários jogos analógicos, como peões e cartas, por exemplo, e também os jogadores em si, enquanto a experiência de jogos estritamente digitais geralmente dificulta a interação face a face.…”
Section: Jogos Híbridosunclassified
“…Segundo elas, essa experiência é facilitada por interações tangíveis, físicas e sociais, que envolvem elementos comuns presentes em vários jogos analógicos, como peões e cartas, por exemplo, e também os jogadores em si, enquanto a experiência de jogos estritamente digitais geralmente dificulta a interação face a face. Jogos de mesa híbridos também são uma plataforma rica para criar e prover novas experiências de jogo, através de recursos como, por exemplo, touch screen, câmera e conectividade online [10].…”
Section: Jogos Híbridosunclassified
“…Finally, because of relying on embedded technology not requiring external hardware, ITo offers a more mobile and cost effective alternative to tabletop and ADI technologies. For more information about the ITo approach see [18].…”
Section: Hybrid Board Games: the Ito Approachmentioning
confidence: 99%